Interdisciplinary care for newborns with cleft lip and palate in a children's multidisciplinary hospital - A. A. Mamedov; Yu. O. Volkov; A. A. Korsunsky; S. A. Parshikova; L. A. Mazurina; L. M. Makarova; Yu. V. Zirkova; G. P. Tukabaev; G. Ma; H. Guo; N. V. Gorlova (Лечащий Врач, 2021)
The accumulated experience of pediatric surgery of newborns and diagnostic methods (CT, MRI, prenatal diagnostics) have made it possible to change the existing terms for the correction of congenital facial defects. The article describes in detail «A system of care for children with cleft lip and palate in the neonatal period», developed and implemented at the Department of Pediatric Dentistry and Orthodontics, Sechenov University. The necessary conditions for rendering assistance to this category of patients are described, indications for pre-surgical preparation are formulated, the tactics of treatment, anesthetic management in this category of newborns are substantiated. The article presents the results of early surgical correction of 46 newborns with cleft lip and palate. Children with cleft lip and alveolar bone were divided into 2 groups. The first group (n = 30) included patients whose diastasis in the area of the alveolar processes was 10 mm or less. In this case, cheilorinoplasty was performed immediately. Group 2 (n = 16) included children with alveolar ridge diastasis of the upper jaw of more than 10 mm. This group of newborns underwent pre-surgical orthodontic preparation for 10-12 days, which consisted of installing ortho-implants and applying an elastic traction chain. The criterion for readiness for surgery was the achievement of a diastasis width between the fragments of the alveolar process of 10 mm or less. This was followed by simultaneous removal of ortho-implants and surgery – cheilorinoplasty. Newborns with a cleft of the hard and soft palate (n = 4) underwent uranoplasty according to the method of A. A. Mamedov. All patients received good aesthetic and functional results.